Pertanggungjawaban Pidana atas Deepfake AI dalam Produksi dan Distribusi Pornografi Digital di Indonesia - Kevin David Sirait; Arman Saut Rivando; Cecilia Angel; Zico Ricardo Aritonang; Lenny Maria Aritonang (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The development of deepfake technology based on Artificial Intelligence has given rise to complex manipulative digital pornography crimes. This study analyzes the legal framework and criminal liability in Indonesia. The results show that regulations such as the Pornography Law and the ITE Law have not specifically regulated deepfake, creating a legal vacuum. Nevertheless, perpetrators can be prosecuted interpretatively through existing provisions. Regarding criminal liability, perpetrators who produce and distribute deepfake pornographic content can be held accountable if the elements of actus reus and mens rea are fulfilled. However, there are obstacles in evidence and perpetrator identification due to anonymity and the borderless nature of digital technology.